Pengaruh Pembiayaan Mikro Syariah dan Pengetahuan Penyusunan Laporan Keuangan Terhadap Perkembangan UMKM (Studi Kasus Anggota BWM Usaha Mandiri Sakinah Yogyakarta) - Muti’ah, Nurul; Retnaningdiah, Dian (Kajian Ekonomi dan Bisnis, 2020)
The purpose of the study was to determine the effect of the provision of Islamic microfinance and knowledge of financial report preparation on the development of UMKM. This study used a descriptive quantitative method and the data sourced was from primary data and secondary data. Data were collected by using questionnaires and literature study. The sample used was the customer or member of BWM Usaha Mandiri Sakinah Yogyakarta as many as 78 respondents. The sample was obtained by using the simple random sampling method. Method of Analysis: Data analysis used in this study was the Multiple Linear Regression Test. Financing partially affects UMKM development is in accordance with what was hypothesized, knowledge of Financial Report Preparation has a partial effect on variable UMKM development , this is in accordance with what was hypothesized. Simultaneously, Sharia Micro Financing and Knowledge of Financial Report Preparation affect UMKM Development, this result is in accordance with the hypothesis.